Pengembangan Media Pembelajaran Interaktif Autoplay Media Studio 8.5 Pada Materi Gejala-Gejala di Atmosfer dan Hidrosfer - H. M. Maskam; Marta Putra Dinata; Armin Subhani (Geodika: Jurnal Kajian Ilmu dan Pendidikan Geografi, 2020)
This research is based on the ineffectiveness of textbook based learning. The purpose of this study is to produce effective learning media based on validity. Learning media developed based on AutoPlay Media Studio 8.5. This learning media is applied to social studies subjects, especially on symptoms in the atmosphere and hydrosphere learning material. The research location was carried out at Tembeng Putik Islamic Junior Secondary School, East Lombok, NTB. This research design uses research and development. Data were collected using media validation sheets, teacher response instruments and learning achievement tests. The results showed that the validity of the media was declared very valid with a percentage of 91.83%. For practicality based on the teacher's response to the media is very good with a percentage of 93.12%. Whereas student learning outcomes after using the media based on AutoPlay Media Studio 8.5 were stated to be good with a percentage of mastery learning outcomes of 84%. Thus it can be concluded that this media can be used as a supporter of the learning process of social studies subjects in the phenomenon of symptoms in the atmosphere and hydrosphere in Tembeng Putik Islamic Junior Secondary School.